Correction of osteopetrosis in the neonate oc/oc murine model after lentiviral vector gene therapy and non-genotoxic conditioning - Penna, Sara; Zecchillo, Alessandra; Di Verniere, Martina; Fontana, Elena; Iannello, Valeria; Palagano, Eleonora; Mantero, Stefano; Cappelleri, Andrea; Rizzoli, Elena; Santi, Ludovica; Crisafulli, Laura; Filibian, Marta; et al. (Frontiers in Endocrinology, 2024)
Introduction: Autosomal recessive osteopetrosis (ARO) is a rare genetic disease, characterized by increased bone density due to defective osteoclast function. Most of the cases are due to TCIRG1 gene mutation, leading to severe bone phenotype and death in the first years of life. The standard therapy is the hematopoietic stem cell transplantation (HSCT), but its success is limited by several constraints. Conversely, gene therapy (GT) could minimize the immune-mediated complications of allogeneic HSCT and offer a prompt treatment to these patients.The Tcirg1-defective oc/oc mouse model displays a short lifespan and high bone density, closely mirroring the human condition. In this work, we exploited the oc/oc neonate mice to optimize the critical steps for a successful therapy.Results: First, we showed that lentiviral vector GT can revert the osteopetrotic bone phenotype, allowing long-term survival and reducing extramedullary haematopoiesis. Then, we demonstrated that plerixafor-induced mobilization can further increase the high number of HSPCs circulating in peripheral blood, facilitating the collection of adequate numbers of cells for therapeutic purposes. Finally, pre-transplant non-genotoxic conditioning allowed the stable engraftment of HSPCs, albeit at lower level than conventional total body irradiation, and led to long-term survival and correction of bone phenotype, in the absence of acute toxicity.These results will pave the way to the implementation of an effective GT protocol, reducing the transplant-related complication risks in the very young and severely affected ARO patients.